Immunotherapy against experimental canine visceral leishmaniasis with the saponin enriched-Leishmune((R)) vaccine - Santos, F. N.; Borja-Cabrera, G. P.; Miyashiro, L. M.; Grechi, J.; Reis, A. B.; Moreira, M. A. B.; Martins Filho, O. A.; Luvizotto, M. C. R.; Menz, I.; Pessoa, L. M.; Goncalves, P. R.; Palatnik, M.; et al. (Elsevier B.V., 2007)
In order to assess the immunotherapeutic potential on canine visceral leishmaniasis of the Leishmune (R) vaccine, formulated with an increased adjuvant concentration (1 mg of saponin rather than 0.5 mg), 24 mongrel dogs were infected with Leishmania (L.) chagasi. The enriched-Leishmune (R) vaccine was injected on month 6, 7 and 8 after infection, when animals were seropositive and symptomatic. The control group were injected with a saline solution. Leishmune (R)-treated dogs showed significantly higher levels of anti-FML IgG antibodies (ANOVA; p < 0.0001), a higher and stable IgG2 and a decreasing IgG I response, pointing to a TH1 T cell mediated response. The vaccine had the following effects: it led to more positive delayed type hypersensitivity reactions against Leishmania lysate in vaccinated dogs (75%) than in controls (50%), to a decreased average of CD4+ Leishmania-specific lymphocytes in saline controls (32.13%) that fell outside the 95% confidence interval of the vaccinees (41.62%, CI95% 43.93-49.80) and an increased average of the clinical scores from the saline controls (17.83) that falls outside the 95% confidence interval for the Leishmune (R) immumotherapy-treated dogs (15.75, CI95% 13.97-17.53). All dogs that received the vaccine were clustered, and showed lower clinical scores and normal CD4+ counts, whereas 42% of the untreated dogs showed very diminished CD4+ and higher clinical score. The increase in clinical signs of the saline treated group was correlated with an increase in anti-FML antibodies (p < 0.0001), the parasitological evidence (p = 0.038) and a decrease in Leishinania-specific CD4+ lymphocyte proportions (p = 0.035). These results confirm the immunotherapeutic potential of the enriched-Leishmune (R) vaccine. The vaccine reduced the clinical symptoms and evidence of parasite, modulating the outcome of the infection and the dog's potential infectiosity to phlebotomines. The enriched-Leishmune (R) vaccine was subjected to a safety analysis and found to be well tolerated and safe. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: FML-vaccine; immunotherapy; Leishmune((R)) vaccine; canine visceral leishmaniasis; Leishmania chagasi; kala-azar; saponin; Quillaja saponaria molina; QS21